Factors influencing undergraduates to purchase the viral marketing products / Syafirah Suhaimi - Suhaimi, Syafirah (Faculty of Business and Management, 2019)
The purpose of this is to investigate the factors influencing selected students to purchase the viral marketing products. To add this study used four independent variables which are brand recommendation, market maven, peer socialization, and family socialization meanwhile the dependent variable which is purchase intention. To add, this study is focusing on selected students of UiTM Melaka, City Campus. There were 160 respondents as sample size based on questionnaires returned and also used 7 point Likert Scale as instrument. Besides, this study used Descriptive Analysis, Reliability Analysis, Correlation Analysis, and Multiple Regression Analysis and data analysis was conducted using Statistic Packages for Social Science (SPSS) software version 25. Based on the results, all independent variables have significant relationship towards dependent variable.